Diary of a wimpy kid : the long haul - Kinney, Jeff. (New York : Amulet Books, 2014)
The Heffley family road trip starts off full of promise, then quickly takes several wrong turns--with everything from a fender bender to crazed seagulls--but even the worst road trip can turn into an adventure, and this is one the Heffleys will not soon forget.
Keywords: Automobile travel -- Fiction; Vacations -- Fiction; Family life -- Fiction; Diaries -- Fiction; Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / General